Prediction of the functional significance of the left main stenosis using frequency domain optical coherence tomography. (14th October 2021) - Vlad, D; Bouki, P; Nakas, A; Diamantakis, E; Kotsakis, A; Baroutsi, K; Toutouzas, K
Abstract: Background: Frequency domain optical coherence tomography (FD-OCT) has been used for the assessment of non-ostial left main coronary artery stenosis (LM). However, no study has evaluated the use of this imaging technique for the prediction of functional significance of LM lesions determined by the fractional flow reserve (FFR). Purpose: The aim of this study was to assess the safety and diagnostic efficacy of FD-OCT in identifying functional severity of the LM stenosis determined by (FFR). Methods: One hundred one patients with LM lesion (20–70% diameter stenosis angiographically) underwent FFR measurement and FD-OCT imaging of the LM. The following parameters were measured by FD-OCT in the LM: reference lumen area (RLA), reference lumen diameter (RLD), minimum lumen area (MLA), minimum lumen diameter (MLD), % lumen area stenosis, % diameter stenosis. Results: The LM lesions were visible and measurable by FD-OCT in 88/101 (87.1%) patients. However lesions with ostial location were analyzable by FD-OCT only in 17/30 (56.4%) patients (Figure 1). FFR at maximum hyperemia was ≤0.80 in 39/88 (44.3%) patients. FFR values were correlated significantly with FD-OCT derived LM lumen parameters. Receiver operating characteristic curves showed that an MLA cutoff value of 5, 38 mm 2 had the highest sensitivity and specificity of 82% and 81% respectively (Figure 2A), followed by an MLD of 2.43 mm (sensitivity 77%, specificity 72%) (Figure 2B) and an %AS of 60% (sensitivity 72%, specificity 72%) (Figure 2C) for predicting FFR ≤0.80. Conclusions: FD-OCT is safe and feasible imaging technique for the assessment of a LM stenosis except the ostial LM lesions which are analyzable in half of the cases. An FD-OCT derived MLA of ≤5.38 mm 2 strongly predicts the functional severity of a LM lesion. Funding Acknowledgement: Type of funding sources: None.